Novel Coupled Molecules from Active Structural Motifs of Synthetic and Natural Origin as Immunosuppressants - Minhas, Richa; Bansal, Gulshan; Bansal, Yogita (Medicinal Chemistry, 2020)
Introduction: Nitric oxide (NO) is an important mediator in the pathogenesis and control of immune system-related disorders and its levels are modulated by inducible NO synthase (iNOS). Oxidative stress is another pathological indication in majority of autoimmune disorders. The present study aims at the development of coupled molecules via selection of pharmacophores for both immunomodulatory and antioxidant activities through iNOS inhibition. Methods: Variedly substituted coumarin moieties are coupled with naturally occurring phenols through an amide linkage and were predicted for activities using computer-based program PASS. The compounds predicted to have dual activities were synthesized. Docking studies were carried out against iNOS (PDB 1R35) and compounds having good docking score were evaluated for immunomodulatory and antioxidant activities. Results: The synthesized compounds were found to be pure and were obtained in good yields. Compounds with maximum docking score (YR1a, YR2e, YR2c and YR4e) were selected for evaluation by in vitro models. Compounds YR2e and YR2c markedly inhibited the reduction of NBT dye and showed maximum % iNOS inhibition. In DPPH assay, compound YR4e was observed as the most potent antioxidant (EC50 0.33 μM/mL). Based on these studies, compounds YR2e and YR2c were selected for haemagglutination test. Compound YR2e was observed as the most active immunosuppressant with maximal inhibitory ability of iNOS and NBT reduction and lower HAT value of 3.5. Conclusion: Compound YR2e can be utilized as a pharmacological agent in the prevention or treatment of immunomodulatory diseases such as tumors, rheumatoid arthritis, ulcerative colitis, organ transplant and other autoimmune disorders.
Keywords: iNOS